Dust Devil Frequency of Occurrence and Radiative Effects at Jezero Crater, Mars, as Measured by MEDA Radiation and Dust Sensor (RDS). Issue 1 (23rd January 2023) - Toledo, D.; Apéstigue, V.; Arruego, I.; Lemmon, M.; Gómez, L.; Montoro, F.; Hueso, R.; Newman, C.; Smith, M.; Viudez‐Moreiras, D.; Martínez, G.; Lorenz, R.; et al.
Abstract: The Mars Environmental Dynamics Analyzer, onboard the Perseverance rover, is a meteorological station that is operating on Mars and includes, among other sensors, the radiometer Radiation and Dust Sensor (RDS). From RDS irradiance observations, a total of 374 dust devils (DDs) were detected for the first 365 sols of the mission (Ls = 6°–182°), which along with wind and pressure measurements, we estimated a DD frequency of formation at Jezero between 1.3 and 3.4 DD km −2 sol −1 (increasing as we move from spring into summer). This frequency is found to be smaller than that estimated at the Spirit or Pathfinder landing sites but much greater than that derived at InSight landing site. The maximum in DD frequency occurs between 12:00 and 13:00 local true solar time, which is when the convective heat flux and lower planetary boundary layer IR heating are both predicted to peak in Jezero crater. DD diameter, minimum height, and trajectory were studied showing (a) an average diameter of 29 m (or a median of 25 m) and a maximum and minimum diameter of 132 ± 63.4 and 5.6 ± 5.5 m; (b) an average minimum DD height of 231 m and a maximum minimum‐height of 872 m; and (c) the DD migration direction is in agreement with wind measurements. For all the cases, DDs decreased the UV irradiance, while at visible or near‐IR wavelengths both increases and decreases were observed. Contrary to the frequency of formation, these results indicate similar DD characteristics in average for the studied period. Plain Language Summary: Dust devils are dry, dusty convective vortices that play a key role in the dust cycle on Mars by lifting dust from the surface to the atmosphere. Parameters like the dust devil formation frequency or size characteristics are key to constrain their contribution to the planet's dust budget. Using observations made by the Radiation and Dust Sensor of the instrument Mars Environmental Dynamics Analyzer onboard Perseverance rover, we estimated the dust devil (DD) frequency for the full diurnal cycle in Jezero crater, Mars, during the first half of the Martian year. We find that between 1 and 3 DD per km −2 form every day, mainly around noon, and they become more frequent as spring advances to summer. The formation frequency is smaller than that estimated at the Spirit landing site but much greater than the values derived at InSight landing site, indicating a high variability in activity depending on location. When the DDs blocked the direct sunlight from reaching the sensor, we estimated their diameters to range between 5 and 130 m with an average of 29 m. In all detections, the presence of DDs resulted in a decrease of the measured UV radiation. Key Points: A dust devil frequency of occurrence of between 1.3 and 3.4 dust devils km −2 sol −1 was derived from MEDA‐RDS observations for the first 365 sols, displaying the maximum activity at around noon and increasing as we move from spring into summer We find an average dust devil diameter of 29 m (or a median diameter of 25 m) and maximum and minimum diameters of 132 ± 63.4 m and 5.6 ± 5.5 m Dust devil migration directions are in agreement with the MEDA background wind direction measurements